Cookups.com: An entrepreneurial initiative linking home kitchens to consumers. Issue 1 (10th April 2023) - Ahmed, Jashim U.; Talukdar, Amreen; Faroque, Anisur R.; Ahmed, Asma
This case study is based on the companyCookups.com (hereafter Cookups), an initiative started by a woman who has changed the culinary dimension of business by bringing home cooks together under one platform. This case presents the institutional entrepreneurship journey of the first culinary platform of home cooks in Bangladesh, which benefits and facilitates female entrepreneurs who would otherwise be unemployed. Starting with the sociocultural aspects, the case study analyzes the various elements of the "cloud kitchen" and the factors that make this business model sustainable even in the midst of the COVID-19 pandemic. Cookups has been a pioneering effort in the field of women's empowerment in the country, ensuring that women of all social backgrounds and classes have access to a platform to generate income. The case study also aims to discover the various challenges a startup can face in its mode of operation and how to overcome them using technological solutions.